PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM PADA BAGIAN IT MENGGUNAKAN “10-STEP KM ROADMAP” (STUDI KASUS: UNIT STI ITTP) - Nurul Ayuni Jingga Putri; Yudha Saintika; Dwi Januarita (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
The implementation of an IT system in an organization or company can help improve the performance of knowledge management implementation. By having good knowledge management, managed organizations can become more effective, efficient and well structured. The System and Information Technology Unit (STI) is a technical unit that accommodates all digital services needed by every community at IT Telkom Purwokerto. However, the problem that occurs in the System and Information Technology Unit (STI) is that the existing knowledge is not recorded properly. The design of a Knowledge Management System can help organizations document and record existing knowledge of staff and store it in a knowledge database so that it is easier to access. The design carried out in this study is to use the "10-Step KM Roadmap" by implementing 6 Steps. The data collection method used in this study is a qualitative research method by conducting interviews, observing and documenting the data collected. The results of this study are in the form of a blueprint document containing an analysis of the knowledge management system design, functional & non-functional system requirements, KM Team design, use case diagrams, activity diagrams, and class diagrams. The knowledge management system recommendation is described in the form of a wireframe as an overview of the system to be built. Keywords: knowledge management, knowledge management system, System and Information Technology Unit (STI), 10-Step KM Roadmap